2018
DOI: 10.17235/reed.2018.5338/2017
|View full text |Cite
|
Sign up to set email alerts
|

Complete splenic embolization for the treatment of refractory ascites after liver transplantation

Abstract: Refractory ascites is an uncommon complication that may develop postoperatively after liver transplantation. The diagnosis and treatment of this condition is a real challenge. We report two cases of patients who underwent a transplant due to cryptogenic cirrhosis and developed refractory ascites during the immediate postoperative period. This is a serious complication associated with decreased survival by up to one year and a reduced quality of life. After ruling out the main causes of ascites, a portal hyperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This is particularly important in high-flow vessels where there is risk of distal migration of coils. 13,21 A previous systematic review and metaanalysis 23 revealed that distal embolization at small arterial branches within the splenic parenchyma may lead to splenic infarction or increase the risk of splenic abscess formation. Proximal embolization at the main splenic artery may decrease the risk of infarction because the rich network of collateral circulation from the left gastric, gastroepiploic arteries, pancreatic, and omental branches enters the spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important in high-flow vessels where there is risk of distal migration of coils. 13,21 A previous systematic review and metaanalysis 23 revealed that distal embolization at small arterial branches within the splenic parenchyma may lead to splenic infarction or increase the risk of splenic abscess formation. Proximal embolization at the main splenic artery may decrease the risk of infarction because the rich network of collateral circulation from the left gastric, gastroepiploic arteries, pancreatic, and omental branches enters the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several studies have investigated SAE as the treatment of IA after liver transplantation. 5,7,8,10,13 However, the choices of different embolic materials used in SAE still need to be discussed. Even though SAE using AVP and coils has been described, 12 the therapeutic efficacy and outcomes between AVP and coils for patients with IA after livingdonor liver transplantation (LDLT) have not been established.…”
mentioning
confidence: 99%
“…Graft inflow or PVP modulation is at the forefront of these treatments. Portosystemic shunting techniques or preservation of collateral veins[ 19 , 47 - 50 ], as well as splenectomy or splenic artery ligation/embolization[ 51 - 53 ], are effective ways to address post-transplantation portal hyperperfusion. In cases where the GRWR of grafts is very low, dual grafts can be considered[ 54 ].…”
Section: Small-for-size Grafts In Ldltmentioning
confidence: 99%